2014
DOI: 10.1039/c3ce42382d
|View full text |Cite
|
Sign up to set email alerts
|

The diversity of Zn(ii) coordination networks composed of multi-interactive ligand TPHAPvia weak intermolecular interaction

Abstract: Seven types of different Zn(TPHAP) coordination networks were prepared thanks to the excellent multi-interactivity of TPHAP via weak intermolecular interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…Interestingly, the 0.40 m m solution (green line) showed a significant intensity increase at 300 and 360 nm with a slight shoulder at 400 nm, which can be assigned to an H‐aggregation dimer for the former and a J‐aggregation dimer for the latter with a J‐type higher oligomer, according to the exciton theory . In fact, we have also revealed that K + TPHAP − tends to form the salt‐bridging dimer as indicated by CSI‐MS measurements . At 2.0 m m (light blue line), the peak at 360 nm almost completely disappeared and the intensities at 380 nm and 400 nm increased.…”
Section: Resultssupporting
confidence: 51%
See 4 more Smart Citations
“…Interestingly, the 0.40 m m solution (green line) showed a significant intensity increase at 300 and 360 nm with a slight shoulder at 400 nm, which can be assigned to an H‐aggregation dimer for the former and a J‐aggregation dimer for the latter with a J‐type higher oligomer, according to the exciton theory . In fact, we have also revealed that K + TPHAP − tends to form the salt‐bridging dimer as indicated by CSI‐MS measurements . At 2.0 m m (light blue line), the peak at 360 nm almost completely disappeared and the intensities at 380 nm and 400 nm increased.…”
Section: Resultssupporting
confidence: 51%
“…In fact, we have demonstrated that TPHAP − can trap the kinetic states of PCNs . The multi‐interactivity of TPHAP − produced various metastable networks by changing only solvents or additives in the reactions . These results indicate that the solution states of TPHAP − , i.e., monomer or aggregation, greatly affect the morphological features of the networks.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations